Effects of turbocharger rotational inertia on engine and turbine performance in a turbocharged gasoline direct injection engine under transient and steady conditions. (January 2022) - Park, Chansoo; Ebisu, Motoki; Bae, Choongsik
The effects of turbocharger (T/C) rotational inertia on engine and turbine performance under transient and steady engine conditions were analyzed in a 2.0 L 4-cylinder turbocharged-gasoline direct injection (T-GDI) engine. The test T/Cs consisted of heavy and light compressor wheels (C/W) and turbine wheels (T/W). The study was conducted in two research stages. First, transient engine load tests were conducted to evaluate the effect of T/C rotational inertia on transient response of the T/C, combustion performance, and fuel consumption. Seconds, steady engine load tests were conducted to find out if a light inertia T/C can run at higher efficiency under the same exhaust pulsating flow conditions within one engine cycle. In order to evaluate the engine on-board turbine instantaneous performances in the units of crank angle degree (CAD), T/C rotation speed and pressure data were measured in the experiment. The instantaneous exhaust gas mass flow rate and the temperature of upstream and downstream of the turbine were extracted by 1-D simulation. Turbine efficiency and mass flow rate parameters were calculated by combining these data. In the results, there existed positive effects of light inertia T/C on response and specific fuel consumption under transient conditions. It was also found that the light inertia T/C could show higher T/C speed fluctuation under the same exhaust pulsating flow conditions. Consequently, blade speed ratio (BSR) and turbine efficiency of light inertia T/C were partially higher than that of conventional one. However, it was not led to higher engine efficiency.